2007
DOI: 10.1037/1528-3542.7.2.354
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable effects of conscious emotion regulation strategies on explicit and implicit memory.

Abstract: The authors manipulated emotion regulation strategies at encoding and administered explicit and implicit memory tests. In Experiment 1, participants used reappraisal to enhance and decrease the personal relevance of unpleasant and neutral pictures. In Experiment 2, decrease cues were replaced with suppress cues that directed participants to inhibit emotion-expressive behavior. Across experiments, using reappraisal to enhance the personal relevance of pictures improved free recall. By contrast, attempting to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
184
8
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(223 citation statements)
references
References 55 publications
30
184
8
1
Order By: Relevance
“…These results support and extend our previous study (Nielson et al, submitted for publication) that showed better long-term retrieval (without the post-learning modulation manipulation) for these words in low reappraisers. However, the current results contrast with previous studies, which used short-term retention tests, and found either no effects of reappraisal on memory (Egloff et al, 2006;Richards & Gross, 1999) or enhanced retrieval in reappraisal (Dillon et al, 2007;Richards & Gross, 2000).…”
Section: Reappraisalcontrasting
confidence: 99%
See 1 more Smart Citation
“…These results support and extend our previous study (Nielson et al, submitted for publication) that showed better long-term retrieval (without the post-learning modulation manipulation) for these words in low reappraisers. However, the current results contrast with previous studies, which used short-term retention tests, and found either no effects of reappraisal on memory (Egloff et al, 2006;Richards & Gross, 1999) or enhanced retrieval in reappraisal (Dillon et al, 2007;Richards & Gross, 2000).…”
Section: Reappraisalcontrasting
confidence: 99%
“…Previous studies have generally shown that suppression leads to reduced retrieval of high arousing, and in some cases low arousing, stimuli after short-term retention tests, in the absence of differences relative to the subjective experience of the stimuli (Bonanno et al, 2004;Dillon et al, 2007;Egloff et al, 2006;Richards, 2004;Richards & Gross, 1999, 2000. Our previous study (Nielson et al, submitted for publication), however showed that while there were no subjective differences in the experience of the stimuli, retention testing delayed by 1-week led to no memory reduction in suppression.…”
Section: Suppressionmentioning
confidence: 99%
“…Although emotion regulation research has gained an increasing interest recently (Ochsner & Gross, 2005), the vast majority of functional neuroimaging studies to date tended to focus on the effect of cognitive control on the immediate emotional experience, rather than on the effect on memory (but see Dolcos, Sung, Denkova, Dixon, & Dolcos, 2011). Specifically, it is unclear how the engagement of various cognitive control strategies affect the impact of emotion on memory (but see Dillon et al, 2007), and the underlying neural circuitry. Investigation of the neural mechanisms underlying the effect of emotion regulation on memory processes has relevance to understanding clinical conditions such as depression and anxiety, in which emotion dysregulation is often among the core debilitating features.…”
Section: Discussionmentioning
confidence: 99%
“…If that was the case, given the evidence that some emotion regulation strategies increase emotional memory (Dillon, Ritchey, Johnson, & LaBar, 2007), preserved emotional enhancement of memory in aging could be a 'byproduct' of enhanced emotion regulation. These findings involving negative emotions, along with findings from studies investigating similar effects involving positive emotions (see also Kensinger & Schacter, 2008), are consistent with the positivity bias in remembering emotional memories reported in aging (Mather, 2006;Mather & Carstensen, 2005).…”
Section: Age-related Differencesmentioning
confidence: 99%
“…A number of studies have shown that they have different underlying cognitive mechanism (e.g., Dillon, Ritchey, Johnson, & LaBar, 2007). Thus, the second goal of the current study was to investigate what specific effects of reward and punishment have on conflict processing when they were explicitly associated with task-relevant dimension (ink color) and when they were implicitly associated with task-irrelevant dimension (word's semantic meaning) respectively.…”
mentioning
confidence: 98%